Managing technology in the operations function - Loader, David
'Managing Technology in The Operations Function' looks at issues in technology from the operations function rather than from an IT perspective. It explores the use of technology for processing, provision of client services, risk management and business management. The authors analyse the benefits of straight through processing and the practical implications of managing technology products in operations. System risk and opportunities are explored and case studies are examined along with industry trends to assess upcoming developments and their impacts. The use of technology is one of the key dr.